Laryngeal Collapse in Brachycephalic Dogs - Wells, Jamie E. (Tufts University. Tisch Library., 2023)
The goal of the following study is two-fold: first, to explore the possibility of external stenting as a surgical correction of laryngeal collapse, and second, to perform a retrospective analysis of medical records to describe risk factors and disease outcomes among brachycephalic breeds diagnosed with laryngeal collapse.; Cummings School Summer Scholar 2021.